Reflections of a Muslim-Portuguese maritime world in a sixteenth-century Portuguese source - Salimi, Abdulrahman al-; Staples, Eric (Proceedings of the Seminar for Arabian Studies, 2015)
This paper discusses a record of expenses of an early sixteenth-century Portuguese vessel, the Santa Maria do Monte, during its voyage from Goa to Hormuz and back in 1520-1521, stopping in the Omani ports of Qalhāt, Ṭīwī, Qurayyāt, Muscat (Masqat), and Khawr Fakkān along the way. The route sailed during this voyage is examined in light of regional navigational practices, and the composition of the crew is discussed, emphasizing the significant non-Portuguese population on board. The nature of the ship and the specific costs of maintaining this vessel during the voyage are also addressed. Collectively, the cultural intersections involved with the navigation, the crew, and the maintenance regime of this vessel provide specific examples of maritime relationships in the region. In terms of its broader significance, such evidence of a high concentration of regional actors in a Portuguese instrument of maritime power alludes to a more complex and interdependent relationship between the Portuguese and the Arabian Sea maritime spheres. It also highlights a specific segment of the vibrant maritime Indian Ocean mosaic that the Portuguese were compelled to navigate during their imperial endeavours.
Keywords: Relations – Oman – Portugal

جهاد اليعاربة ضد الاستعمار البرتغالي 1033-1131م/1624-1718م - سعد, نيفين مصطفى حسن (مجلة بحوث الشرق الأوسط, 2017)
Number: 041
Keywords: Relations – Oman – Portugal

التصدي العثماني للبرتغاليين في مسقط: 1551م – 1581م - الهاشمي, سعيد بن محمد (2012)
Keywords: Relations – Oman – Portugal

« Portugal in the Sea of Oman » : les fonds documentaires du Portugal et les récits des voyageurs ibériques au début du XVIIe siècle - Couto, Dejanirah (2016)
Keywords: Relations – Oman – Portugal

Oman and Omanis in Portuguese sources in the Early Modern Age (1500 - 1750) - Teles e Cunha, João (2011)
Keywords: Relations – Oman – Portugal

The Portuguese in East Africa and the Omani reconquest of East Africa - Newitt, Malyn (2011)
Keywords: Relations – Oman – Portugal

Oman E Portugal (1650-1730) Política E Economia - Busaidi, Ibrahim Yahya Zahran (Universidade de Lisboa, 2010)
Keywords: Relations – Oman – Portugal

Portugal in the sea of Oman: religion and politics: research on documents - Salimi, Abdulrahman al-; Jansen, Michael (von Zabern, 2012)
Keywords: Relations – Oman – Portugal

Arshīf al-Wathā’iq al-Burtughāliyya fī Baḥr ʿUmān: Qirā’a fī ‘l-Siyāq al-Tārīkhī - Ismāʿīlī, Aḥmad (Al-Minhāj, 2015)
Keywords: Relations – Oman – Portugal

Omani-Portuguese maritime activities (1500-1650 CE) - Floor, Willem (Oman: a maritime history, 2017)
Keywords: Relations – Oman – Portugal

Portuguese Colonization in Omani Literature: The Image of National Identity and Resistance - Hajri, Hilal al- (Local and global Ibadi identities, 2019)
Keywords: Relations – Oman – Portugal

Oman and Omanis in Portuguese Sources in the Early Modern Period (ca. 1500-1750) - Cunha, João Teles e (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal

The Portuguese in East Africa and the Omani Reconquest of East Africa - Newitt, Malyn (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal